The Indigenous Education Experience in Algeria: A Reformist Project within Intellectual Tensions - tahi, ismail (Journal of Social Sciences and Humanities, 2016)
Independent Algeria inherited a hybrid educational system composed of French education, free Arabic education, and traditional religious (Kuttab/Zaouia-based) schooling, with these three forms operating simultaneously. The French school provided an education identical to that implemented in metropolitan France in terms of legislation, curricula, language, and content. However, this educational model, with all its components, did not correspond to the cultural and national foundations of the Algerian people, nor to the aspirations of a nation that had sacrificed its best youth to restore its dignity and recover its Arab-Islamic identity, aiming to re-establish the country’s authentic Arab-Islamic character while fostering religious and social awareness consistent with national principles. The second type was free Arabic education, inherited from the nationalist movement. It is well known that the Association of Algerian Muslim Ulema established schools and institutes across cities and rural areas, and many of these classes remained open even after independence.